Consórcio público de saúde como instrumento de organização do atendimento dos pacientes vitimas de trauma na região Sudoeste do Paraná - Barreto, Adelar Monteiro (2025)
The creation of the National Emergency Care Policy (PNAU) marks a new paradigm for medical emergency care, with the establishment of two of its main components: the Mobile Emergency Care Service (SAMU 192) and the Medical Regulation Center (CRM). This situation required changes in the organization of the medical emergency care network. The implementation of the PNAU, through the public health consortium, significantly contributes to the operationalization of the SUS principles, breaking down geographic and economic barriers. This study aimed to analyze the care process for trauma victims in southwestern Paraná after the creation of the Intermunicipal Consortium of the Southwest Paraná Emergency Network (CIRUSPAR). This study aims to understand CIRUSPAR's role in the care process for trauma victims in southwestern Paraná and discuss its contributions to regional development. This research is characterized by document analysis and data analysis, with a qualitative approach. Semi-structured interviews were conducted, and the interviewees were divided into groups according to their involvement in the care process: CRM managers; municipal managers; state managers; and hospital administrators. In addition to the interviews, official documents were also surveyed, including accident reports from the Paraná State Highway Police, the Federal Highway Police, and accident reports attended by SAMU for the year 2024. Data triangulation revealed that trauma care, when provided through a network between CRM, SAMU, and referral hospitals, benefits patients from a reduced risk of death and sequelae. Consortium municipalities benefit from the financial sharing of service maintenance costs, which allows them to implement the PNAU.